Screenwriting : Creative Labor and Professional Practice. - Conor, Bridget (Milton : Taylor & Francis Group, 2014)
Screenwriting: Creative Labor and Professional Practice analyzes the histories, practices, identities and subjects which form and shape the daily working lives of screenwriters. Author Bridget Conor considers the ways in which contemporary screenwriters navigate and make sense of the labor markets in which they are immersed.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books